A Systematic Review on the Impact of Internal Remittances on Poverty and Consumption in Developing Countries: Implications for Policy - Housen, Tambri; Hopkins, Sandra; Earnest, Jaya (John Wiley & Sons Ltd, 2012)
This paper reviews the current literature on the usage and impact of internal remittances on recipient households in low-income countries. A systematic review was conducted using six electronic and four informal databases. Using narrative synthesis, we reviewed 18 studies. The results of the review provide strong evidence revealing that internal migration is an important poverty reduction strategy with remittance shaving the greatest impact on the poorest households. Internal migrant remittances serve not only to improve livelihood by decreasing the household depth and severity of poverty but also increase household investment in education and housing. This review proposes recommendations for policy and future internal remittances research.